(untitled) (Praxis Educativa, 2023)
Through their establishment, societies create their temporality asan emergence of alterity and d ifference, which implies their present and future project for society and individuals. However, with the expansion of neoliberal capitalism that undertakes the evacuation of the past, our current time is considered unique and infinite, jeopardizing the future project that society would offer the subjects. From this perspective and based on what young Mexicans pro pose about the future, the article reflects on the project that contemporary society provides to young people, who, in their creative processes of identity, appeal to the imaginary meanings that the community has to offer them to conformas subjects and articulate their desires in future-to-future projects.